2012
DOI: 10.3390/ijms13067559
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymorphisms of the Lipoprotein Lipase Gene and Their Association with Coronary Artery Disease in the Saudi Population

Abstract: Coronary heart disease (CHD) is a major health problem and a major cause of death in most countries. Evidence has been presented that gene polymorphisms (HindIII, PvuII and Ser447Ter) of lipoprotein lipase (LPL) are risk factors of coronary artery disease (CAD).AimOur objective of the present investigation was to determine whether 3 LPL polymorphisms (LPL-HindIII, LPL-PvuII and LPL-Ser447Ter) can be considered as independent risk factors for CAD in the Saudi population.MethodsWe recruited 120 CAD subjects, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…This result were in agreement with observation of [33] which found that the frequency of the S447 was significantly higher in healthy subjects than in coronary artery disease, while the frequency of the X447allele was significantly higher in coronary artery disease as it amounted to rate of 83% compared to healthy group as amounted to rate of 61%. It also found [34] that the patient's with cardiovascular the Turkish they had a high in the frequency of the X447 allele as amounted to rate of 29.2% compared to healthy group as amounted to rate of allele frequency X447 of 17.39% .…”
Section: Discussionsupporting
confidence: 93%
“…This result were in agreement with observation of [33] which found that the frequency of the S447 was significantly higher in healthy subjects than in coronary artery disease, while the frequency of the X447allele was significantly higher in coronary artery disease as it amounted to rate of 83% compared to healthy group as amounted to rate of 61%. It also found [34] that the patient's with cardiovascular the Turkish they had a high in the frequency of the X447 allele as amounted to rate of 29.2% compared to healthy group as amounted to rate of allele frequency X447 of 17.39% .…”
Section: Discussionsupporting
confidence: 93%
“…A few studies have reported that the polymorphisms of HindIII, Ser447X and PvuII were associated with the risk of CAD [ 10 , 12 , 13 , 14 ]. However, these results were also controversial [ 14 , 15 , 16 , 17 ]. Some studies found no association between these gene variants of LPL and the risk of CAD [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these results were also controversial [ 14 , 15 , 16 , 17 ]. Some studies found no association between these gene variants of LPL and the risk of CAD [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is one of the greatest causes of morbidity and mortality worldwide being responsible for a high percentage of death annually in different countries (Al-Jafari et al, 2012). CAD is a multifactorial disorder believed to result from an interaction between the genetic background and environmental factors such as diet, smoking and physical activity (Daoud et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is usually associated with conventional risk factors including hypertension, diabetes mellitus, dyslipidemia and smoking (Rustempasic et al, 2014). In recent years, many studies started to explore the relationship between CAD and the common variants of genes central to lipid metabolism (Al-Jafari et al, 2012andTurlo et al, 2014. The lipoprotein lipase (LPL) gene, which spans; 35 kilobases on chromosome 8p22 is composed of 10 exons separated by 9 introns and encodes the mature form of LPL (Tanguturi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%